2013
DOI: 10.1002/app.39585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular architecture on the crystalline structure and stiffness of iPP homopolymers: Modeling based on annealing experiments

Abstract: Five PP homopolymers were selected and their molecular structure was thoroughly characterized to determine the effect of molecular architecture on their annealing behavior and on the ultimate stiffness achieved by heat treatment. Molecular mass and its distribution were characterized by rheological measurements, while chain regularity was determined by calorimetry, by the stepwise isothermal segregation technique (SIST). The samples were annealed in two different ways. Tensile bars were treated in an oven at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
(51 reference statements)
2
16
0
Order By: Relevance
“…These simulated results indicate that the desired mechanical properties can be achieved if crystallinity is around 75% and lamella thickness is larger than 30 nm. This is in good agreement with our earlier results that 3 GPa of modulus can be reached by carefully designed annealing experiments [38].…”
Section: Empirical Modeling Of Stiffness Using Structural Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…These simulated results indicate that the desired mechanical properties can be achieved if crystallinity is around 75% and lamella thickness is larger than 30 nm. This is in good agreement with our earlier results that 3 GPa of modulus can be reached by carefully designed annealing experiments [38].…”
Section: Empirical Modeling Of Stiffness Using Structural Parameterssupporting
confidence: 93%
“…Based on the earlier results [7,38] and our experimental data it can be concluded that stiffness depends predominantly on crystallinity and lamella thickness. Consequently, the following expression should be solved (Equation (9)):…”
Section: Empirical Modeling Of Stiffness Using Structural Parameterssupporting
confidence: 68%
See 1 more Smart Citation
“…Despite that, the crystallization during SSA-DSC is influenced by the presence of nucleating agents and kinetics especially in the samples of NPP2 and NPP3, which contain both UHMW fraction and nucleating agent. The presence of UHMW fraction hinders the crystallization [29] at high temperature resulting in apparently smaller chain regularity in these samples. Moreover, we have to emphasize that the evaluation of NMR results is much more complicated than that of SSA-DSC traces.…”
Section: Effect Of the Evaluation Techniquementioning
confidence: 95%
“…The modulus of crystalline polymers is determined mainly by crystallinity and the thickness of the lamella grown during crystallization [65]; lamella thickness increases with increasing crystallization temperature, thus also with nucleation [66,67]. The heat of fusion proportional to crystallinity is plotted against additive content in Figure 5.…”
Section: Structurementioning
confidence: 99%